Sustainable recovery of wastewater to be reused in cooling towers: Towards circular economy approach. (June 2021) - Arias, Borja Garrido; Merayo, Noemi; Millán, Alejandro; Negro, Carlos
Graphical abstract: Highlights: Sustainable recovery of wastewater from bottle washing and disinfection. Complete degradation of H2 O2 through catalytic decomposition. Acid washed activated carbon as catalyst of H2 O2 decomposition. 100 % recycled water in the real industrial cooling towers. Full functionality in maintenance and industrial hygiene of cooling towers. Abstract: Circular economy approach is needed in order to move towards sustainable development. In this frame, the current work is aimed at improving the sustainability of a food industrial plant through circular economy approach, using a waste stream, coming from the washing and disinfection of bottles before product packaging, as source of water for the cooling process. The implementation of this approach is much more relevant in sectors that are water-intensive, such as food and beverages industry. The wastewater produced as results of the washing process has quite high quality, therefore, there reuse in the cooling process is justified. However, it is needed to previously remove the hydrogen peroxide present in that wastewater stream to protect refrigeration circuits from oxidation. Hydrogen peroxide is produced as a result of the decomposition of peracetic acid, which is used as disinfection agent in the washing process, being acetic acid the other byproduct. In order to remove the hydrogen peroxide, catalytic decomposition of hydrogen peroxide with activated carbon was performed, studying both required contact time for different activated carbon/hydrogen peroxide ratios and kinetic models of hydrogen peroxide decomposition at lab scale. Subsequently, the proposed solution was applied at industrial scale, achieving 100 % water replacement in cooling towers. The solution performed in this case can be easily replicated in other plants using peracetic acid as disinfectant.